Inside Front Cover. Issue 5 (11th September 2022) - Unknown
Abstract : Here, a triphenylamine‐PDI (perylene diimide) polymer photocatalyst with an oxidative ability was prepared. By introducing an electron‐donating motif, the D‐A structure was constructed. The introduction of the triphenylamine motif promoted charge separation and improved the performance. Photocatalytic oxidation of N‐heterocycles used a green oxidant air in a water‐based solution at room temperature. This work provides the feasible use of semiconductor photocatalysts in selective oxidation, with practical application potential. Abstract : Here, a triphenylamine‐PDI (perylene diimide) polymer photocatalyst with an oxidative ability was prepared. By introducing an electron‐donating motif, the D‐A structure was constructed. The introduction of the triphenylamine motif promoted charge separation and improved the performance. Photocatalytic oxidation of N‐heterocycles used a green oxidant air in a water‐based solution at room temperature. This work provides the feasible use of semiconductor photocatalysts in selective oxidation, with practical application potential.